Mapping Portfolio IT Investment by Perception Level Management and IT investments toward Organization Performance (Case study : BPR Mustika Utama Kolaka Southeast Sulawesi) - Ningsi, Nurfitria; Pribadi Subriadi, Apol (Institut Teknologi Sepuluh Nopember, 2017)
This research intended to give an overview on the micro banking to develop the concrete steps of IT infrastructure to facing the globalization of business. Previous studies showed that the differences in the perception of negative effect on long-term performance of the organization in this case the productivity paradox. Mapping IT Investment Portfolio as an approach to user orientation be appropriate alternative to achieving objective business success by offering a wide range of potential applications with objective of user needs. This study finding there are 15 potential applications that can be developed by Micro banking for 5 years later with specific application indeed to reflecting all levels of management needs.